2014
DOI: 10.1186/2193-1801-3-691
|View full text |Cite
|
Sign up to set email alerts
|

Statistical design and optimization of single cell oil production from sugarcane bagasse hydrolysate by an oleaginous yeast Rhodotorula sp. IIP-33 using response surface methodology

Abstract: Single cell oil production from sugarcane bagasse hydrolysate by oleaginous yeast Rhodotorula sp. IIP-33 was analyzed using a two stage statistical design approach based on Response Surface Methodology. Variables like pentose sugar, (NH4)2SO4, KH2PO4, yeast extract, pH and temperature were found to influence lipid production significantly. Under optimized condition in a shake flask, yield of lipid was 2.1199 g with fat coefficient of 7.09 which also resembled ~99% similarity to model predicted lipid production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…According to the ANOVA results, the (NH 4 ) 2 SO 4 concentration showed a significant negative effect on lipid concentration and lipid content (data not shown). This was also observed by Bandhu et al [43] who found from BBD that (NH 4 ) 2 SO 4 concentration had significant negative effect on lipid concentration. Consequently, a decrease of the (NH 4 ) 2 SO 4 concentration led to enhanced lipid concentration together with lipid content.…”
Section: Optimization Of the Concentration Of (Nh 4 ) 2 So 4 Kh 2 Psupporting
confidence: 82%
“…According to the ANOVA results, the (NH 4 ) 2 SO 4 concentration showed a significant negative effect on lipid concentration and lipid content (data not shown). This was also observed by Bandhu et al [43] who found from BBD that (NH 4 ) 2 SO 4 concentration had significant negative effect on lipid concentration. Consequently, a decrease of the (NH 4 ) 2 SO 4 concentration led to enhanced lipid concentration together with lipid content.…”
Section: Optimization Of the Concentration Of (Nh 4 ) 2 So 4 Kh 2 Psupporting
confidence: 82%
“…This was mainly attributed to the presence of P and S in these mineral salts. Because, in the literature, it is stated that carbon source is directed to cell growth in the presence of excessive P and S but to lipid synthesis under P and S limited conditions (Bandhu et al, 2014;González-García et al, 2017;Ortucu et al, 2017;Elfeky et al, 2019). The experiments revealed that NaCl concentrations up to 5 g/L significantly stimulated lipid synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme solution was added after the cassava residue solution was cooled to approximately 40°C and the pH was adjusted to 4.0. Samples were then maintained at 30°C on a 150 r min −1 shaker .…”
Section: Methodsmentioning
confidence: 99%